A construção social da crítica das práticas jornalísticas: dispositivos críticos na esfera pública em rede - Coelho, Diônatas Álisson (Universidade do Vale do Rio dos Sinos, 2019)
This thesis is dedicated to an analysis of manifestations of criticism to Brazilian journalism carried out in a network. The research starts from the identification of different critical apparatus engendered by society and then to understand the strategies mobilized by the social actors to question the constructions of reality coming from journalism. The apparatus were mapped from the study of five cases of great repercussion in the Brazilian press in which journalism was strongly criticized by network participants. Mapping the apparatus, we proceed to an analysis of the dynamics that occur within each of them to finally perceive the points of contact between the critical devices. Our theoretical basis is based on the quest to understand this new networked public sphere and the dynamics realized by the network society. Then we analyze the manifestations that occur in this environment in the deepening in the understanding of what are apparatus, for then, to discuss criticism and devices of criticism. It is concluded in the study that the criticism of the journalistic practices is a social construction, that uses of contributions of at least five main socially elaborated apparatus. We call these five apparatus critical social commentary, occasional controversial professional critique, academic criticism, professional criticism, and the ombudsman. The criticisms built into each device are strategically circulated by other apparatus, in a constant and systemic critical flow that generates exchanges between different participants. The result of these articulations we come to understand as the social construction of the criticism of journalistic practices.
Keywords: Jornalismo; Crítica das práticas jornalísticas; Sociedade em rede; Dispositivos críticos; Crítica de mídia; Journalism; Critique of journalistic practices; Networked society; Critical apparatus; Media Criticism; ACCNPQ::Ciências Sociais Aplicadas::Comunicação